Two-point method: A quick and fatigue-free procedure for assessment of muscle mechanical capacities and the 1 repetition maximum. - Garcia-Ramos, A.; Jaric, S. (Strength and Conditioning Journal, 2018)
The force-velocity relationship is used to evaluate the maximal capacities of active muscles to produce force, velocity, and power. The load-velocity relationship has also been used to predict the 1 repetition maximum (1rm) and, consequently, the relative loads (%1rm). The 2-point method has recently emerged as a quick and fatigue-free procedure for the assessment of both the force-velocity and load-velocity relationships. This article summarizes the results of previous studies that have explored the feasibility of the 2-point method and provides practical recommendations for its application by strength and conditioning professionals.